Dama Kameliowa - Dumas, Alexandre, 1824-1895.; Dumas, Alexandre, 1824-1895. (Warszawa : Comfort Oficyna Wydawn., 1992)
The classic Dumas tale of the courtesan who falls in love with a nobleman, "The Lady of the Camelias."